2012
DOI: 10.1136/thoraxjnl-2012-202678.144
|View full text |Cite
|
Sign up to set email alerts
|

P3 Oxidative Distress and Antioxidants in Severe Asthma: Abstract P3 Table 1

Abstract: Poster sessionsThorax 2012;67(Suppl 2):A1-A204 A65could be impaired rather than AO deficiency. This needs to be researched further in larger studies. Adherence assessment prior to Omalizumab initiation was completed by all centres; however there was a varied approach of each centre in their assessment. 90.6% assessed prescription records, 74.4% questioned patients regarding medication adherence, 32.5% measured prednisolone levels and 4.6% utilised a validated questionnaire (4.6%) Longitudinally 48.8% continue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several authors confirmed they were unable to measure 8-isoprostane in a majority of their samples (54)(55)(56). Of those studies in this review which reported undetectable samples the percentage ranged from 16% (Komakula et al) to 50% (Piotrowski et al).…”
Section: Page 16 Of 27 Author Submitted Manuscript -Jbr-100456r1mentioning
confidence: 97%
“…Several authors confirmed they were unable to measure 8-isoprostane in a majority of their samples (54)(55)(56). Of those studies in this review which reported undetectable samples the percentage ranged from 16% (Komakula et al) to 50% (Piotrowski et al).…”
Section: Page 16 Of 27 Author Submitted Manuscript -Jbr-100456r1mentioning
confidence: 97%